NEUROBEHAVIORAL AND NEUROCHEMICAL EVALUATION OF EPIDERMAL GROWTH FACTOR RECEPTOR (EGFR) INHIBITOR –GEFITINIB IN Β-AMYLOID OLIGOMER INDUCED ALZHEIMER'S DISEASE IN MICE MODEL - Jagadeesh Dhamodharan1,2,Ganthimathy Sekhar2, Arunachalam Muthuraman3* (JOURNAL OF PHARMACEUTICAL ANALYSIS, 2024)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder that accounts for about 60-80% of dementia cases globally.Currently used AD drugs provide only symptomatic management with lots of adverse effects. A drug with potential curative for AD with negligible adverse effects remains to be investigated. Gefitinib (GE) is anepidermal growth factor receptor(EGFR) inhibitor, commonly used as monotherapy innon-small cell lung cancer and other solid tumours. Very few studies have shown the memory rescuing capacity of GE.Aim: Therefore the present study was designed to investigate the neuroprotective Donepezil, intracerebroventricular injection, novel object recognition, neurotoxin, neuron-specific enolase.